Towards regional access to medicines: the development of the East African Community pooled procurement mechanism - Koray Parmaksiz; Domina Asingizwe; Alison Kaitesi Gichohi; Stephen Karengera (Taylor & Francis Group, 2024)
Introduction The East African Community (EAC) has been facing challenges in ensuring access to affordable and quality-assured medicines. To address these problems, the EAC Partner States have been working on implementing an inter-country pooled procurement mechanism since 2005. However, with limited progress to date. The aims of this study were to explore how the EAC pooled procurement mechanism has been developing over time, and to clarify the work and efforts made during this development process to draw lessons for enhancing such collaborative efforts.Methods For this study, we carried out a multi-method qualitative case study. We used the Pooled Procurement Guidance to collect and structure our data drawn from academic papers, grey literature documents, observations and field notes. For the analysis, we used an inductive thematic analysis approach.Results Over the past two decades of the EAC's pooled procurement journey, we have identified two developmental stages so far: the promise stage and the creation stage. The promise stage was characterised by initial engagement and alignment efforts between Partner States. However, the lack of dedicated funding and ownership to drive the project forward led to stagnation of the process for some years. Following the establishment of a dedicated organisation, the pooled procurement mechanism entered the creation stage. This stage has been characterised by continuous alignment work consisting of project management, efforts to build inter-personal relationships, and facilitation of negotiations to harmonise goals, needs and operations. This process has been aided by broad and recurring involvement of regional experts.Conclusion To successfully implement a pooled procurement mechanism, we suggest EAC Partner States to continue their alignment efforts, sustain political will and allocate sustainable funding using a phased implementation approach towards pooled procurement.